Increasing the Organizational Green Performance through Green HRM Practices and Islamic Spiritual Intelligence - Anwar, Mohammad Ziad; Jati, Lalu Jatmiko; Zahrah, Zahrah (CV The Journal Publishing, 2023)
Studi ini bertujuan untuk melakukan kajian empiris mengenai strategi peningkatan organizational green performance melalui green HRM dan Islamic spiritual intelligence. Studi ini dilakukan kepada 144 pekerja Small and Medium Enterprises (SMEs) di Nusa Tenggara Barat. Studi ini menggunakan pendekatan survei, kemudian data diuji dengan pendekatan structural equation model (SEM) yang spesifik pada alat analisis partial least square (PLS). Penelitian ini pada akhirnya mengkonfirmasi green HRM dan Islamic spiritual intelligence berpengaruh positif dan signifikan terhadap employee green behavior. Selain itu, employee green behaviour juga ditemukan berpengaruh langsung secara positif dan signifikan terhadap organizational green performance, dan menjadi pemediasi pada pengaruh green HRM dan Islamic spiritual intelligence terhadap organizational green performance. Studi ini menghadirkan sejumlah keaslian yang memberikan keunikan daripada studi-studi sebelumnya yang relevan, pertama, studi ini fokus pada kajian mengenai peran domain individu yang spesifik pada Islamic spiritual intelligence pada perilaku ramah lingkungan karyawan, mayoritas studi di Indonesia lebih banyak melibatkan domain individu yang spesifik pada kepribadian untuk menjelaskan fenomena perilaku dan kinerja ramah lingkungan. Kedua, studi ini fokus pada implementasi teori dasar person-environment fit theory dalam menjelaskan peran Islamic spiritual intelligence dan praktik green HRM pada peningkatan perilaku dan kinerja ramah lingkungan, beberapa peneliti dan akademisi di Indonesia masih relatif jarang mengeksplorasi peran teori dasar yang mapan dalam bidang manajemen sumber daya manusia dan organisasi untuk menjelaskan fenomena kinerja ramah lingkungan organisasi. Temuan pada studi ini dapat memberikan sejumlah kontribusi positif dalam pengembangan teori ramah lingkungan di bidang SDM, dan dapat diimplementasikan sebagai strategi dalam praktik peningkatan kinerja ramah lingkungan organisasi. Kata kunci; Organizational Green Performance, Green HRM, Islamic Spiritual Intelligence, Employee Green Behavior Abstract: This study aims to conduct an empirical study regarding strategies for increasing organizational green performance through green HRM and Islamic spiritual intelligence. This study was conducted on 144 Small and Medium Enterprises (SMEs) workers in West Nusa Tenggara. This research uses a survey approach, then the data is tested using a specific structural equation modeling (SEM) approach using the partial Least Square (PLS) analysis tool. This research confirms that green HRM and Islamic spiritual intelligence have a positive and significant effect on employees' green behavior. Apart from that, employees' green behavior also has a direct positive and significant effect on organizational green performance and mediates the influence of green HRM and Islamic spiritual intelligence on organizational green performance. This study presents a number of originalities that provide uniqueness compared to previous relevant studies, first, this study focuses on studying the role of individual domains specific to Islamic spiritual intelligence on employee green behavior, most studies in Indonesia involve more individual domains. specific to personality to explain the phenomenon of green behavior and performance. Second, this study focuses on implementing the basic theory of person-environment fit theory in explaining the role of Islamic spiritual intelligence and green HRM practices in improving green behavior and performance. Several researchers and academics in Indonesia still relatively rarely explore the role of established basic theories in the field of human resources management and organizations to explain the phenomenon of organizational green performance. The findings in this research can provide several positive contributions to the development of green theory in the HR field and can be implemented as a strategy for improving the performance of green organizations.